STUDY COMPARISON OF TRIAXIAL TEST WITH MULTISTAGE AND CONVENTIONAL METHOD ON SANDSTONES - ROSADI BUDIMAN (NIM 12102028); Pembimbing: Dr. Ir. Suseno Kramadibrata, M.Sc., ARDIAN
Multistage triaxial is a test method in which testing a single rock specimen under more than one confining pressures, whereas that of conventional one is a method in which testing multiple rock specimens under dif ferent confining pressures. The multistage method consist s of multiple loading stages and each stage is terminated when the rock specimen is about to fail. In this study, rock specimens cored from a common block of sandstones which was taken from PT. XYZ, ROTO NORTH, Pit 4 were then tested using both the conventional and the multistage triaxial testing methods. The multistage triaxial test used axial stress as a termination point on each stage. Similar trends were founded when the triaxial test results were analyzed using Mohr-Coulomb and Hoek & Brown criterion. Cohesion (c) that is resulted from the multistage triaxial test is greater than that of the conventional triaxial test (20,6% in Hoek & Brown criterion and 35,9% in Mohr-Coulomb criterion). On the other hand, internal friction angle (O) which is resulted from the multistage triaxial test is smaller than that of the conventional triaxial test (5,7% in Hoek & Brown criterion and 7,1% in Mohr-Coulomb criterion). This difference is caused by the reduction of rock specimen strength after being loaded at the first stage. Every stage of loading in multistage triaxial test is terminated when the rock specimen is about to fail.